Hybrid-fiber reinforced engineered cementitious composite under tensile and impact loading. (5th March 2017) - Ali, M.A.E.M.; Soliman, A.M.; Nehdi, M.L.
Abstract: The behavior under impact loading of an innovative hybrid fiber-reinforced engineered cementitious composite incorporating short randomly dispersed shape memory alloy (HECC-SMAF) and PVA fibers was explored using a drop weight impact test. Test specimens were also heat-treated to investigate possible pre-stressing effects of SMA fibers on the impact resistance of the ECC. Uniaxial tensile testing on ECC coupon specimens was also conducted. A two-parameter Weibull distribution was used to analyze variations in experimental results in terms of reliability function. Results indicate that SMA fibers significantly enhanced the tensile and impact performance of the ECC. Adding fibers beyond a certain dosage led to fiber clustering, thus, no further gain in tensile and impact performance was measured. The impact resistance of HECC-SMAF specimens was further improved after exposure to heat treatment. This highlights the significant contribution imparted by the local pre-stressing effect of SMA fibers to the impact resistance of the composite. The Weibull distribution was adequate to predict the impact failure strength of ECC, allowing to avert additional costly experiments. This research underscores the potential to engineer new cementitious composites with superior tensile properties and impact resistance for the protection of critical infrastructure in the event of explosive or impact loading. Graphical abstract: Highlights: New SMA-PVA engineered cementitious composite was developed. SMA fibers offer local pre-stress effect in the novel composite. Novel SMA-PVA hybrid composite offers superior performance under impact. Composite has potential in design of critical infrastructure for homeland security.